ANALISIS KINERJA KEUANGAN KELOMPOK BANK BERDASARKAN MODAL INTI 1 (KBMI 1) SEBELUM DAN SESUDAH DIBERLAKUKANNYA POJK FINANCIAL TECHNOLOGY - Amalia Putri Kusuma, (2022)
This research aims to determine the differences in the financial performance of the Bank Group Based on Core Capital I (KBMI I). The sample of this study is the Group of Banks Based on Core Capital 1 (KBMI 1) registered with the Financial Services Authority from 2015 to 2020 with an observation period of three years before the implementation of POJK fintech and three years after the implementation of POJK fintech, with probability sampling technique obtained as many as 51 companies. the sample in this study. By using SPSS 26 assistance and analysis techniques Paired Sample T-Test and Wilcoxon Sign Rank Test, the results of this study are that there are differences in profitability before and after the implementation of POJK fintech and there are no differences in liquidity and bank capital of KBMI I before and after the implementation of POJK. Fintech.